Heterologous prime-boost cellular vaccination induces potent antitumor immunity against triple negative breast cancer - Niavarani, Seyedeh-Raheleh; St-Cyr, Guillaume; Daniel, Lauren; Lawson, Christine; Giguère, Hugo; Alkayyal, Almohanad A.; Tai, Lee-Hwa (Frontiers in Immunology, 2023)
Triple negative breast cancer (TNBC) is the most aggressive and hard-to-treat subtype of breast cancer, affecting 10-20% of all women diagnosed with breast cancer. Surgery, chemotherapy and hormone/Her2 targeted therapies are the cornerstones of treatment for breast cancer, but women with TNBC do not benefit from these treatments. Although the prognosis is dismal, immunotherapies hold significant promise in TNBC, even in wide spread disease because TNBC is infiltrated with more immune cells. This preclinical study is proposing to optimize an oncolytic virus-infected cell vaccine (ICV) based on a prime-boost vaccination strategy to activate these tumor infiltrated immune cells. We used various classes of immunomodulators to improve the immunogenicity of whole tumor cells in a prime vaccine, followed by their infection with oncolytic Vesicular Stomatitis Virus (VSVd51) to deliver a boost vaccine. We observed that treatment of TNBC-bearing mice with the influenza virus-modified prime vaccine followed by the VSVd51 infected boost vaccine coupled with early surgical resection resulted in the best survival. Taken together, this novel adjuvant cancer vaccination strategy could be a promising therapeutic avenue for TNBC patients.